Cinética da presença de vasos sanguíneos no processo de reparo ósseo alveolar em camundongos - Mata, Ananda Resende da (2018)
Bone repair is a dynamic tissue reaction, which presents different steps, such as: inflammation, cell proliferation and synthesis of extracellular matrix. Among the possible strategies for therapeutic of alveolar bone repair, we can highlight the modulation in the presence and formation of blood vessels, which is extremely important to the process of bone repair, whose kinetics are not yet deeply understood. The present study aims to analyze the kinetics of blood vessels and to correlate it with the volume of clot and bone tissue. The study consists in preparation and histological analysis to verify different histological cells, structures and tissues. As a result we obtained a clot formation in the 0 hour period, presence of neovascularization on the 7th day, a partial bone filling of the central portion of the alveolus in the period of 14 days and finally the repair of the dental alveolus. In this way, this research verified a direct connection between the angiogenic phenomena in the immune and chemotactic response in a condition of bone tissue repair.